THE EFFECT OF CREDIT RISK AS A MEDIATOR BETWEEN LIQUIDITY AND CAPITAL ADEQUACY ON BANK PERFORMANCE IN BANKING COMPANIES LISTED ON THE IDX - Julia Safitri; Ana Kadarningsih; Maaz Ud Din; Sri Rahayu (Jurnal Penelitian Ekonomi dan Bisnis, 2020)
Liquidity is one of the main factors faced by banking companies because its main relationship is channeling funds from third parties with bank performance. This study aims to examine credit risk which is proxied by Raroc (return adjusted on risk capital) as a mediator of the effect of liquidity (loan to deposit ratio) on the bank performance (return on assets). The analytical tool used in this study is SEM-WarpPLS 5.0, this study shows that credit risk can mediate the effect of liquidity on bank performance. This shows that the greater the credit risk, the smaller the bank's performance.Keywords: Financial Intermediation Theory; Liquidity; Bank Performance.